Analytical Study of the Grand Slam Judo Championship / Abu Dhabi 2017 - Mohameed, Zahar (Journal of Physical Education, 2017)
The researcher designed the basis of this analytical study, to be an informationalresource for judo specialists from all academics and coaches, as well as players.The study aimed to analyze the technical performance of the competitions of thistournament, and the relationship of this performance technical points and penalties inaccordance with the updates of the new law of judo sport.Several data collection channels were used:1. Live viewing of streams.2. Video filming.3. Monitoring device for the registration plate (a special device for the International JudoFederation).4. Personal interviews with coaches of participating national teams.Several aspects of the analysis were also highlighted:1. Katami Waza-Nakki Waza (Ground Play Skills - Shooting Skills).2. Obtain the full point (IPON) relative to the full download time.3. Record the technical points and change the registration plate relative to the time of the fulldownload.4. Recording technical points during bleeding.5. Sanctions recorded on players.Through the results and presentation, the researchers explained the importance ofthe analysis and its procedures during judo tournaments. The impact of international lawupdates on changing competition techniques was also highlighted.